Frequency of pathogens associated with cervical lymphadenitis in guinea pigs of family-commercial breeding centers in Cusco, Peru - Angulo-Tisoc, José (2021)
The aim of this study was to identify and evaluate the antibiotic susceptibility of the main bacterial pathogens isolated from cases of cervical lymphadenitis in guinea pigs from two commercial-family breeding centres in the province of Canchis, Cusco. In total, 64 samples of cervical abscesses were processed between September 2018 and March 2019. The samples were cultured and the antibiogram on agar with discs of the main antibiotics used in family-commercial rearing systems was carried out. Beta-hemolytic Streptococcus sp (91.8%, 56/61), Staphylococcus sp (45.9%, 28/61) and Klebsiella sp (21.3%, 13/61) were identified. The highest frequency of isolates occurred in adult guinea pigs. The frequency of antimicrobial susceptibility was high for all the isolated genera, except for enrofloxacin and trimethoprim-sulfamethoxazole for beta-hemolytic Streptococcus sp. The results show a diversity of bacterial agents present in cervical lymphadenitis, as well as a low frequency of antibiotic resistance.